1991
DOI: 10.1172/jci115118
|View full text |Cite
|
Sign up to set email alerts
|

Gelsolin-related amyloidosis. Identification of the amyloid protein in Finnish hereditary amyloidosis as a fragment of variant gelsolin.

Abstract: The Finnish type of familial amyloidosis is a systemic disease characterized by progressive cranial neuropathy, corneal lattice dystrophy, and distal sensimotor neuropathy. Amyloid fibrils were isolated from the kidney and heart of a patient with Finnish amyloidosis. After solubilization, the amyloid proteins were fractionated by gel filtration and purified by reverse-phase HPLC. Complete amino acid sequence analyses show that the two amyloid components obtained are fragments of gelsolin, an actin-modulating p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…In this heritable disease, Asp-187, which is part of the G2 Ca-coordination sphere, is mutated to Asn or Tyr (20). The mutant proteins are unable to bind Ca 2ϩ at this site and can be predicted to have three abnormalities with regard to Cadependent activation.…”
Section: Loss Of G2 Ca Binding In Fafmentioning
confidence: 99%
See 2 more Smart Citations
“…In this heritable disease, Asp-187, which is part of the G2 Ca-coordination sphere, is mutated to Asn or Tyr (20). The mutant proteins are unable to bind Ca 2ϩ at this site and can be predicted to have three abnormalities with regard to Cadependent activation.…”
Section: Loss Of G2 Ca Binding In Fafmentioning
confidence: 99%
“…The second, to the activated state, occurs at Ϸ10 M to 1 mM Ca 2ϩ (17)(18)(19). A single mutation within the type 2 metal ion-binding site in G2-of Asp-187 to Asn or Tyr-is the cause of familial amyloidosis Finnish-type (FAF), characterized by the extracellular deposition of a 71-residue fragment of gelsolin (20). It has been proposed that this mutation destabilizes gelsolin through loss of Ca coordination at the type 2 site in G2 (10), making it susceptible to cleavage by furin in the acidic trans-Golgi compartment (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mutations (D187N/Y) causing gelsolin amyloidosis disrupts Ca 2+ binding within domain 2 which makes it susceptible to aberrant cleavage by furin yielding a secreted 68 kDa fragment referred to as C68 [319,320]. The C68 fragment is further cleaved in at least two positions by metalloprotease(s) producing 8 (residues A173-M243) and 5 kDa (residues A173-R225) gelsolin fragments which compose the amyloid deposits in patients [321,322]. Far-UV CD analysis of the amyloidogenic A173-M243 fragment of the D187N gelsolin revealed that this protein being substantially unfolded possesses structural features typical of the pre-molten globule [323].…”
Section: Gelsolin and Finnish-type Familial Amyloidosismentioning
confidence: 99%
“…In the rare Finnish type of FAP, a variant of gelsolin (3) has been identified; and in FAP of the Iowa type, a variant of apolipoprotein AI (apoAI) (4,5), the major apolipoprotein of high density lipoprotein (HDL) (6), has been reported. The apoAl Iowa variant protein, with arginine substituted for glycine at position 26, has also been found postmortem in a single patient with non-neuropathic hereditary systemic amyloidosis (7).…”
mentioning
confidence: 99%